One-Step Method for the Synthesis of Nitroisoindoles via 1,3-Dipolar Cycloaddition of Azomethine Ylides to Polynitrobenzenes - Starosotnikov, Alexey M.; Bastrakov, Maxim A.; Kachala, Vadim V.; Belyakov, Pavel A.; Fedyanin, Ivan V.; Shevelev, Svyatoslav A. (Synlett, 2012)
A new one-step method for the synthesis of nitroisoindoles was developed on the basis of 1,3-dipolar cycloadditions of unstabilized N-alkyl azomethine ylides with di- and trinitrobenzenes.
Keywords: isoindoles; 1,3-dipolar cycloaddition; nitroarenes; azomethine ylides; heterocycles